IACEE Porto Declaration: A Global Challenge for Engineers - Alfredo Soeiro (2017)
http://international.asee.org/internationalforum/virtual-presentations/ https://peer.asee.org/29283 : https://peer.asee.org/collections/2017-asee-international-forum